Effect of urea super granules, prilled urea and poultry manure on the yield of transplant Aman rice varieties (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh in transplant Aman season 2008 to find out the effect of urea super granules (USG), prilled urea (PU) and poultry manure (PM) on the yield and yield attributes of transplant Aman rice varieties. Two transplant Aman rice varieties viz. BRRI dhan41 and BRRI dhan46 and ten levels of integrated nutrient management encompassing USG, PU and PM were tested following randomized complete block design with three replications. It was observed that variety BRRI dhan41 gave higher grain yield than BRRI dhan46. For fertilizer effect, the highest grain yield (5.17 t ha-1) was obtained from full dose of USG (1.8g) and other inorganic fertilizers, which was similar to that obtained from full dose of USG (1.8g) + PM at 2.5 t ha-1 followed by full dose of PU + PM at 2.5 t ha-1. The lowest grain yield was obtained in the control treatment. In case of interactions, the highest grain yield was obtained in BRRI dhan41×1.8g USG and other inorganic fertilizers which was similar to that of the same dose of USG with PM at 2.5 t ha-1 and the lowest yield was obtained in the control treatment. It was assessed that a considerable portion (31.25%) of PU nitrogen could be saved by using USG (1.8g) together with other inorganic fertilizers or with PM at 2.5 t ha-1. Keywords: Urea super granules; Prilled urea; Poultry manure; Yield; Transplant Aman rice variety DOI: 10.3329/jbau.v7i2.4732 J. Bangladesh Agril. Univ. 7(2): 259-263, 2009